2017
DOI: 10.1080/13813455.2017.1370000
|View full text |Cite
|
Sign up to set email alerts
|

Refeeding after caloric restriction reverses altered liver glucose release

Abstract: Enhanced LGR under caloric restriction is not programmed by early feeding; instead, it is determined by the current nutritional conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…For the most part, results here match those of previous studies Vitoriano et al, 2011;Babata et al, 2014;Garcia et al, 2017): rats under caloric restriction, even after overnight fasting, showed high basal glucose output, responded markedly to the glycogenolytic action of adrenaline and did not increase glucose output in the presence of the gluconeogenic substrate alanine. This metabolic profile is similar to that found in rats in prandial or early post-prandial state -that is, subjected to perfusion soon after feeding (Babata et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…For the most part, results here match those of previous studies Vitoriano et al, 2011;Babata et al, 2014;Garcia et al, 2017): rats under caloric restriction, even after overnight fasting, showed high basal glucose output, responded markedly to the glycogenolytic action of adrenaline and did not increase glucose output in the presence of the gluconeogenic substrate alanine. This metabolic profile is similar to that found in rats in prandial or early post-prandial state -that is, subjected to perfusion soon after feeding (Babata et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Our research group has been reporting changes of liver glucose metabolism caused by caloric restriction since lactation Vitoriano et al, 2011;Babata et al, 2014;Garcia et al, 2017). In those studies, rats from 6-pups litters fed ad libitum after lactation had decreased glucose output and enhanced gluconeogenesis during in situ liver perfusion after overnight fasting, as expected, because fasting decreases liver glycogen stores and favors gluconeogenesis (Rui, 2014).…”
Section: Introductionmentioning
confidence: 73%
See 2 more Smart Citations
“…Glucose output during basal perfusion of the liver represents the release of glucose previously formed and/or stored in the hepatocytes. As the perfusion fluid is devoid of glucose, chemical gradient favors glucose exportation from the liver cells to the fluid [20,21]. After 6 hours at postprandial state, the endogenous stores of glycogen of the mice were, at least, decreased [21], so that a gluconeogenic contribution for glucose output should be considerable.…”
Section: Discussionmentioning
confidence: 99%